Juridical Analysis of Death Penalty Decisions in Drug Cases in Article 114 Law Number 35 of 2009 (Case Study Decision Number 145/PK/Pidsus/2016) - Pranoto, Agung (Greenation Research & Yayasan Global Resarch National, 2024)
Narcotics crimes damage the future of the nation's generations in various aspects of life. Research result; By rejecting the request for review from the applicant for review/convict: FREDI BUDIMAN alias BUDI bin H. NANANG HIDAYAT; means that it does not fulfill the provisions of Article 263 paragraphs (2) and (1) of the Criminal Procedure Code, then based on the provisions of Article 266 paragraph (2) letter a of the Criminal Procedure Code, the request for review from the Judicial Review Applicant/Convict is due to the Judge's error or obvious error in the Judex Facti and Judex Juris decisions. , nor can it be justified because in the Judex Facti and Judex Juris decisions. The judicial review by the Supreme Court is in accordance with the provisions of Article 270 Jo. Article 271 of the Criminal Procedure Code. This is supported by the President's rejection of clemency submitted by convicts on death row for narcotics crimes in accordance with applicable provisions which also automatically stipulate that the court decision has permanent legal force (inkracht van gewijsde). This has also provided legitimacy for the Prosecutor to carry out executions in accordance with the provisions of Article 270 Jo. Article 271 of the Criminal Procedure Code. Author's Suggestions; That the decision can be used as jurisprudence for cases that are similar and have similarities to this case. There is a need to re-evaluate legal findings regarding state officials that provide legal certainty in the field.